IMPLEMENTASI PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DI SMP NEGERI KOTA PADANG - Putri, Natasya Kemala; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ The purpose of this research are three (1) to describe the process of implementatiom of text-based Indonesian language learning, (2) to describe the process of teaching and learning of text-based Indonesian language focused on instructional media, (3) to describe the process of text learning based on the learning material. This research type is qualitative research by using descriptive method. Technique of data collecting is done by observation, interview, and documentation study. The result showed that teachers of SMP Negeri 7 Padang, SMP Negeri 11 Padang, and SMP Negeri 25 Padang have implementated four aspects ofe text-based learning that is at the stage of building the context, studying the model text, constucting guided and constructing independently. Media use in SMP Negeri 7 Padang and SMP Negeri 25 Padang already with excellent category, while at SMP Negeri 11 Padang good category. Teaching material is chosen and determined with consideration and attention to problems, among others (a) the objectives to be achieved for relevance, (b) the scope and its sequence need to be organized in order to be systematic and clear, and (c) time and equipment are also considered.Â Kata kunci: implementasi pembelajaran bebasis teks, media pembelajaran, materi pembelajaran